(untitled) (Contemporary Mathematics, 2023)
This paper elaborates on the approach towards reliability analysis for the active redundant system with a dual nature of repair strategy according to the kind of failure. The reliability characteristics using regenerative techniques are analyzed stochastically for the system, which includes two parallel units acting in an active redundancy form. A transition model has been designed for the working mechanism discussed in the paper and evaluated with the help of a geometric distribution possessing distinct repair. Regenerative techniques and geometric distribution were used to derive the numerical equations for reliability parameters such as availability, mean time to system failure, and repair mechanisms following down period of the system. A graphical analysis of the repair/failure rate with respect to the profit function has also been presented.